Consistent assignment of the vibrations of symmetric and asymmetric ortho-disubstituted benzenes - Tuttle, William D.; Gardner, Adrian M.; Andrejeva, Anna; Kemp, David; Wakefield, Jonathan C.A.; Wright, Timothy G. (Elsevier, 2017)
The form of molecular vibrations, and changes in these, give valuable insights into geometric and electronic structure upon electronic excitation or ionization, and within families of molecules. Here, we give a description of the phenyl-ring-localized vibrational modes of the ground (S₀) electronic states of a wide range of ortho-disubstituted benzene molecules including both symmetrically- and asymmetrically-substituted cases. We conclude that the use of the commonly-used Wilson or Varsányi mode labels, which are based on the vibrational motions of benzene itself, is misleading and ambiguous. In addition, we also find the use of the Mi labels for monosubstituted benzenes [A. M. Gardner and T. G. Wright. J. Chem. Phys. 135 (2011) 114305], or the recently-suggested labels for para-disubstituted benzenes [A. Andrejeva, A. M. Gardner, W. D. Tuttle, and T. G. Wright, J. Molec. Spectrosc. 321, 28 (2016)] are not appropriate. Instead, we label the modes consistently based upon the Mulliken (Herzberg) method for the modes of ortho-difluorobenzene (pDFB) under Cs symmetry, since we wish the labelling scheme to cover both symmetrically- and asymmetrically-substituted molecules. By studying the vibrational wavenumbers from the same force field while varying the mass of the substituent, we are able to identify the corresponding modes across a wide range of molecules and hence provide consistent assignments. We assign the vibrations of the following sets of molecules: the symmetric o-dihalobenzenes, o-xylene and catechol (o-dihydroxybenzene); and the asymmetric o-dihalobenzenes, o-halotoluenes, o-halophenols and o-cresol. In the symmetrically-substituted species, we find a pair of in-phase and out-of-phase carbon-substituent stretches, and this motion persists in asymmetrically-substituted molecules for heavier substituents. When at least one of the substituents is light, then we find that these evolve into localized carbon-substituent stretches.